The Triassic of Traill Ø and Geographical Society Ø, East Greenland: Implications for North Atlantic palaeogeography. (27th July 2018) - Andrews, Steven D.; Decou, Audrey
Abstract : The continental Triassic succession north of 72° in East Greenland has seen little investigation but is key in understanding how facies belts vary towards the East Greenland Shelf, and more widely in the North Atlantic region, through this period. This study presents sedimentological analysis of exposures in northern Traill Ø (the Mols Bjerge) and further north in northern Geographical Society Ø (Laplace Bjerg). These sections are correlated with the more widely studied succession which lies to the south, in Jameson Land and broad scale palaeogeographical reconstructions of the North Atlantic are presented. A largely continental Triassic succession of 1445 m was recorded from the Mols Bjerge. However, a 125 m thick clean sand unit (the Vega Sund Member), which includes in its upper part the Gråklint Beds, is re‐interpreted as of shallow marine origin. Over 1200 m of Triassic strata were recognized on Laplace Bjerg. Within this succession 300 m of clean, cross‐bedded sandstones are recorded and are correlated with the Vega Sund Member recorded in the Mols Bjerge. The northward increase in thickness of marine strata developed at this time provides evidence for a more extensive marine influence in the north. This work has important implications for regional palaeogeographies and the character of the Triassic succession in adjacent basins, in particular, constraining the southern extent of the Boreal Ocean during the Mid to Late Triassic. Furthermore, the correlations made places bitumen staining, reported from Laplace Bjerg, within Triassic strata, suggesting the viability of a Triassic play at depth in adjacent offshore basins.